“Silenciosas, modestas, castas e subservientes”: elas contam suas histórias de vida e mostram que são “boas cumpridoras de seus papéis femininos” - Souza, Joselene Gomes de (2017)
This thesis has, as objective, meet the life stories of women who participate in social movements in the city of Manaus-Am, to analyze the peculiarity of the submission of women in Amazon, understand your ways of architected resistance in a daily life of struggle and inequality, prejudice and discrimination involving the way women is seen historically, in studies and popular sayings. Fruit of a constraining education and creator of stereotypes that determine the roles to men and women in general. We believe the social relations are permeated by exploitation and gender oppression built historically, therefore, develop research with this theme is the way to enable the strengthening of women, their families and the territories inhabited, developing the perception of political entities involved in the fight. Therefore, we can conclude that women suffer from historically according to each culture and geographical space, oppression, invisibility, discrimination, violence among other forms of domination, but they are not submissive, precisely, to understand the submission with act to let master, and the life stories of the women of this research show that they won’t let themselves dominate. The search grows with the methodology of oral history of life. Because he wants to meet the particularity of each woman’s experiences and enable visibility of their experiences and meanings assigned by or them to defend the amazônida woman does not have a particular submission with a greater or lesser degree in relation to Brazilian women in general